Corpos grotescos e fantásticos: a representação feminina nos contos de Angela Carter e Augusta Faro - (:unkn) unknown (Universidade Federal de Goiás, 2017)
This objective work analyzes the construction of the grotesque under the female characters by the bias of the fantastic in the short stories “The Tiger's Bride”, “The Snow Child” and “The Werewolf” from the book The Bloody Chamber (1979) and the short stories “As flores”, “As sereias” and “A gaivota”, by A Friagem (1999) by the writer Augusta Faro. The grotesque revealed itself as an agent for the female characters to enter into a metamorphic process not only on a physical level, but also in the re-signification of language itself, becoming the means for them to question and transgress repressive marks and rules that have long been institutionalized. To reinforce in the analysis we pointed out some aspects: Metamorphosis / The Wild Side, Body Transgressor / Sexuality and Language. We observe how these elements characterized in the grotesque character of the personages and jointly in the communication between the narratives of Angela Carter and Augusta Faro. In order to look at this woman and grotesque relationship, and consecutively at the points of contact that approach the narratives of both writers, the nature of this study is adequate for the theoretical, descriptive, analytical and comparative revision.
Grotescos and fantastic bodies: the feminine representation in the stories of Angela Carter and Augusta Faro
Keywords: Fantástico; Representação feminina; Grotesco; Angela Carter; Augusta Faro; Fantastic; Female representation; Grotesque; LINGUISTICA::FISIOLOGIA DA LINGUAGEM